The Power of a Leader in the Samin People’s Opposition Movement to the Development of a Cement Factory in the North Kendeng Mountains - Enkin Asrawijaya; Bambang Hudayana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
This paper explores the role of a leader in the Samin people’s opposition movement to the construction of a cement factory in the Kendeng Mountains, Java, Indonesia, using Agency Theory. Using Agency Theory can readily explain why the Samin people, who undertook passive opposition to state hegemony, were later able to undertake active and open opposition. Agency became an important factor enabling the Samin people to mount an opposition that was active, open and organized. This agency is about the person of Gunretno. Data were collected using the interview and participation‒observation methods. Interviews were conducted regarding a leader who acted as an agent for opposition actions, and with informants drawn from Samin residential circles and stakeholders who supported the Samin people’s opposition movement. The results revealed that agency is a major contributor to interpreting an opposition movement’s ideological formulation, development of networks, stakeholder support, opposition movement actions of advocacy, and peaceful demonstrations. The Samin people’s opposition actions enhanced their credibility, thus contributing to their movement’s victories through the courts. These findings contribute to social movement theory, particularly in relation to farmers’ movements and traditional communities.